Estatística no Ensino Primário de Angola no período de 2002 a 2020: saberes do ensino e da formação - Eslome Bicicleta (2024)
This research aims to characterize the knowledge to teach and the knowledge to teach Statistics in Primary Education in Angola from 2002 to 2020. Its documentary source was the legislation of the education and teaching system, Primary Education curricula, programs and textbooks of the 5th and 6th grades of the mathematics discipline of the period under study. The central question of the research is: What statistics to teach and to teach were present in Primary Education in Angola in the period from 2002 to 2020? It was covered by theoretical - methodological foundations from a sociocultural perspective, considering authors who highlight the knowledge objectified at the center of the study of teacher professional training, represented by the knowledge to teach and the knowledge to teach articulated together, according to (Hofstetter; Schneuwly), conjectured by hypothesis in mathematics to teach and mathematics to teach, present in the professional training of the teacher who teaches Mathematics (Valente; Bertini; Morais). And, for the process of transforming information into scientific knowledge, analysis was based on Burke's four stages, collection, analysis, dissemination and use, in which Valente reconfigures them into three stages, which are the recompilation of teaching experiences, the comparative analysis of teachers' knowledge, and the systematization and analysis of the use of knowledge as knowledge. The research included elements of the concepts of school culture according to Julia, History of school subjects according to Chervel, History of books and teaching editions according to Choppin. The results of the study indicate that educational systems have always been linked to the socio-political and cultural purposes of the different stages that the country has experienced. The role of the school was not limited to academic activities. The education given and received is the image of the purposes corresponding to the legislation of the respective educational system, in which the purposes outlined for the primary school significantly altered its function, seeking to bring an update in the way of teaching, whose guidelines in the official documents pointed to greater articulation of the discipline with the students' day-to-day situations. These reforms brought a new space and a new teaching and learning relationship that slowly changed concepts and social practices that transformed knowledge in both training and teaching. The programs and textbooks analyzed as a cultural product of a given society responded to the educational purposes of their time, brought together and systematized knowledge to teach and to teach statistics, articulated in mutual dependence and mobilized for the professional training of Mathematics teachers in period under study, which can be characterized as Education Statistics. The analyzes show that the knowledge to teach and teach statistics in primary education is characterized by the production, systematization and organization of content that tends to be elementary and practical, mobilizing arithmetic and objects common to students in this process. Keywords: History of Mathematics Education; Knowing how to teach and to teach; Primary Education in Angola; Statistic; Textbooks.